2021
DOI: 10.1007/s00418-020-01952-z
|View full text |Cite
|
Sign up to set email alerts
|

Simple method of thawing cryo-stored samples preserves ultrastructural features in electron microscopy

Abstract: Preservation of ultrastructural features in biological samples for electron microscopy (EM) is a challenging task that is routinely accomplished through chemical fixation or high-pressure freezing coupled to automated freeze substitution (AFS) using specialized devices. However, samples from clinical (e.g. “biobanking” of bulk biopsies) and preclinical (e.g. whole mouse tissues) specimens are often not specifically prepared for ultrastructural analyses but simply immersed in liquid nitrogen before long-term cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Here, we preserved the porcine myocardium by simply immersing chunks of muscle tissue (∼0.5 cm 3 ) in liquid nitrogen without any pretreatment, seemingly a slow and crude way of preserving tissue, although it is a widely used technique for freezing purified proteins. Similarly, clinical specimens are often preserved in this way and it has been shown that ultrastructural features of such samples can be well conserved when thawed and fixed in glutaraldehyde ( Galhuber et al, 2021 ), consistent with our findings. Strikingly, when flash-freezing (by impact with liquid helium–cooled copper block) is used to ultrarapidly freeze (<10 ms) striated muscle tissue, followed by freeze substitution to chemically preserve frozen components, molecular structural preservation is superb within 5–10 µm of the surface ( Craig et al, 1992 ; Luther et al, 2011 ) but deteriorates rapidly at deeper levels (>10 µm), with severe ice crystal damage apparent (as distortion of the filament lattice; Padron et al, 1988 ).…”
Section: Discussionsupporting
confidence: 90%
“…Here, we preserved the porcine myocardium by simply immersing chunks of muscle tissue (∼0.5 cm 3 ) in liquid nitrogen without any pretreatment, seemingly a slow and crude way of preserving tissue, although it is a widely used technique for freezing purified proteins. Similarly, clinical specimens are often preserved in this way and it has been shown that ultrastructural features of such samples can be well conserved when thawed and fixed in glutaraldehyde ( Galhuber et al, 2021 ), consistent with our findings. Strikingly, when flash-freezing (by impact with liquid helium–cooled copper block) is used to ultrarapidly freeze (<10 ms) striated muscle tissue, followed by freeze substitution to chemically preserve frozen components, molecular structural preservation is superb within 5–10 µm of the surface ( Craig et al, 1992 ; Luther et al, 2011 ) but deteriorates rapidly at deeper levels (>10 µm), with severe ice crystal damage apparent (as distortion of the filament lattice; Padron et al, 1988 ).…”
Section: Discussionsupporting
confidence: 90%
“…The SEM results could provide an important information about the structural composition of adipose tissue layers in the human body, as well as the main microstructural features; however, the sample preparation for SEM measurements should be performed with a special care. Recently it was demonstrated that a simple method of thawing cryo-stored samples preserves ultrastructural features in electron microscopy [132]. In addition, transmission electron microscopy (TEM) was also applied to study the role of adipose tissue function in obesity [133].…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…Electron microscopy of eWAT samples (n = 3 for each HFD-IF and HFD-IF-KO groups) was performed according to a previously published protocol 100 . In short, eWAT was dissected and the bulk tissue immediately flash frozen in liquid nitrogen without cryo-preserving agents.…”
Section: Electron Microscopymentioning
confidence: 99%